2013
DOI: 10.1021/ol400896u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic 1-Alkenylboronates via Zr-Mediated Double Functionalization of Alkynylboronates and Sequential Ru-Catalyzed Ring-Closing Olefin Metathesis

Abstract: Synthesis of novel cyclic 1-alkenylboronates is accomplished through the zirconium-mediated regio- and stereoselective double functionalization of 1-alkynylboronates and the subsequent ruthenium-catalyzed ring-closing metathesis (RCM). The obtained substituted cyclic 1-alkenylboronates are transformed into o-terphenyl and triphenylene derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 76 publications
0
43
0
Order By: Relevance
“…9-Aminophenanthrene 1 was oxidized to tetrabenzocarbazole 2 in 94% yield. Reaction of 2 with Pd(OAc) 2 /tricyclohexylphosphine provided singly fused product 3 in 63% yield 29 . The twisted conformation of 3 was unambiguously elucidated by X-ray diffraction analysis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9-Aminophenanthrene 1 was oxidized to tetrabenzocarbazole 2 in 94% yield. Reaction of 2 with Pd(OAc) 2 /tricyclohexylphosphine provided singly fused product 3 in 63% yield 29 . The twisted conformation of 3 was unambiguously elucidated by X-ray diffraction analysis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alkenylboronates are synthetically versatile building blocks. Despite many reports of the synthesis of alkenylboronates, regio- and stereoselective synthesis of tetrasubstituted alkenylboronates, which are useful precursors for tetrasubstituted alkenes, is particularly challenging. Suginome et al reported seminal examples of the regio- and stereoselective synthesis of tetrasubstituted alkenylboronates through nickel- or palladium-catalyzed intramolecular boryl transfer to a CC triple bond using substrates containing a reactive boryl moiety (Scheme a) . Soon after, palladium- and nickel-catalyzed intermolecular carboboration of alkynes was reported (Scheme b). More recently, copper-catalyzed borylalkylation of alkynes through three-component coupling with bis­(pinacolato)­diboron [(Bpin) 2 ] and alkyl halides has emerged as a powerful method to furnish tetrasubstituted alkenylboronates (Scheme c). , Three main events proceeded in a well-ordered manner in this one-pot, three-component reaction: (1) generation of a borylcopper species from a copper alkoxide catalyst and (Bpin) 2 ; (2) regioselective borylcupration of alkynes to afford alkenylcopper intermediate 1 ; and (3) alkylation of 1 with alkyl halides.…”
mentioning
confidence: 99%
“…[63] Moreover, the cyclic alkenyl boron compounds were also synthesized from this zirconacyclopentene employing the novel ring-closing metathesis with Grubbs catalyst. [64] First, they treated the alkynyl boronate with Negishi's reagent and tributyl phosphine to prepare zirconacyclopropene 61. This produces the zirconacyclopentene 63 via reaction with allyl ether, that undergoes subsequent β-oxygen elimination, and further, a second allylation produces tetrasubstituted alkenyl boronate 64 with two allyl moieties (Scheme 14d).…”
Section: Zirconium Metallacyclementioning
confidence: 99%